Pola Kehidupan Keluarga Petani Jeruk di Desa Katung, Kecamatan Kintamani, Kabupaten Bangli - Ibnu Hajar; I Ketut Darmana; I Gusti Putu Sudiarna (Sunari Penjor : Jurnal of Anthropology, 2019)
The study was conducted in Katung Village, the researcher attempted to provide the description of the life pattern of orange farming in Katung vil-lage vil-lage of Kintamani sub-district. After succeeding in developing the village up to present, the orange farmer commodity is increasingly gain-ing attention from a number of communities to be better developed like other Kintamani areas. anincrease in the number of farmers more than the number of jobs in other fields. This indicates that they have great hopes in the agricultural sector to resolve the demands of liv-ing needs, especially the necessities of life in the family, then of course it will affect the selection of different types of commodities because they are consid-ered more promising better results compared to other types of plants, Like-wise, the management pattern of orange farming that does not always run smoothly from the constraints experienced by farmers today. This study is interesting to study because Katung village is an orange production that needs to be studied specifically.This research is a qualitative research with a de-scriptive analysis approach, which consists of several stages, namely: observation, by interviews with several orange farmers such as: I Wayan Sastono et al. Collecting archives in the form of data population of Katung Villagem such as population growth data, with the area of research-related areas such as the potential they have with a majority farmers. In addi-tion, number of books related to orange farming were used and collaborated with cultural value orientation theories such as Koetjaraningrat's book.